Effect of Botulinum Toxin Type A on TGF-β/Smad Pathway Signaling: Implications for Silicone-Induced Capsule Formation. Issue 5 (November 2016) - Kim, Sena; Ahn, Moonsang; Piao, Yibo; Ha, Yooseok; Choi, Dae-Kyoung; Yi, Min-Hee; Shin, Nara; Kim, Dong Woon; Oh, Sang-Ha
Abstract : Background: One of the most serious complications of breast surgery using implants is capsular contracture. Several preventive treatments have been introduced; however, the mechanism of capsule formation has not been resolved completely. The authors previously identified negative effects of botulinum toxin type A on capsule formation, expression of transforming growth factor (TGF)-β1, and differentiation of fibroblasts into myofibroblasts. Thus, the authors investigated how to prevent capsule formation by using botulinum toxin type A, particularly by means of TGF-β1 signaling, in human fibroblasts. Methods: In vitro, cultured human fibroblasts were treated with TGF-β1 and/or botulinum toxin type A. Expression of collagen, matrix metalloproteinase, and Smad was examined by Western blotting. The activation of matrix metalloproteinase was observed by gelatin zymography. In vivo, the effect of botulinum toxin type A on the phosphorylation of Smad2 in silicone-induced capsule formation was evaluated by immunocytochemistry. Results: In vitro, the phosphorylation of Smad2 was inhibited by botulinum toxin type A treatment. The expression levels of collagen types 1 and 3 were inhibited by botulinum toxin type A treatment, whereas those of matrix metalloproteinase-2 and matrix metalloproteinase-9 were enhanced. Gelatin zymography experiments confirmed enhanced matrix metalloproteinase-2 activity in collagen degradation. In vivo, botulinum toxin type A treatment reduced capsule thickness and Smad2 phosphorylation in silicone-induced capsules. Conclusion: This study suggests that botulinum toxin type A plays an important role in the inhibition of capsule formation through the TGF-β/Smad signaling pathway. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.